1982
DOI: 10.1007/bf01543017
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity to mutation and sister-chromatid-exchange induction in CHO cell mutants defective in incising DNA containing UV lesions

Abstract: Five UV-sensitive mutant strains of CHO cells representing different genetic complementation groups were analyzed for their ability to perform the incision step of nucleotide excision repair after UV exposure. The assay utilized inhibitors of DNA synthesis to accumulate the short-lived strand breaks resulting from repair incisions. After 6 J/m2, each of the mutants showed less than 10% of the incision rate of the parental AA8 cells. After 50 J/m2, the rate in AA8 was similar to that at 6 J/m2, but the rates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
53
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(56 citation statements)
references
References 30 publications
3
53
0
Order By: Relevance
“…If not repaired, SSBs pose a threat to both genetic stability and cell survival, resulting in an increased frequency of mutations and chromosome aberrations (15,23,38,50,53,56). The threat posed by unrepaired SSBs most likely reflects their ability to become double-strand breaks during chromosome replication (27).…”
mentioning
confidence: 99%
“…If not repaired, SSBs pose a threat to both genetic stability and cell survival, resulting in an increased frequency of mutations and chromosome aberrations (15,23,38,50,53,56). The threat posed by unrepaired SSBs most likely reflects their ability to become double-strand breaks during chromosome replication (27).…”
mentioning
confidence: 99%
“…More recently it has been shown that hamster cells preferentially repair certain vital sequences that may facilitate UV resistance despite low overall levels of excision repair (3). It has been suggested that Chinese hamster ovary (CHO) cells with mutations affecting the proficiency of DNA repair pathways may be useful for selecting and assessing the expression of homologous and heterologous DNA repair genes (7,8). Such a mutant CHO cell line has been used recently to select and clone putative DNA repair genes from hamster (9) and human (10,11).…”
mentioning
confidence: 99%
“…The UVsensitive cell line UV135 was derived from parental CHO AA8 cells as previously described (6). UV135 is deficient in the damage site incision step of ER (60). UV-resistant cell line 38.4.4 was derived by two serial genomic DNA transfers into UV135 cells (41).…”
Section: Methodsmentioning
confidence: 99%